ASPEK HUKUM PERLINDUNGAN KONSUMEN DALAM KEBIJAKAN STANDAR NASIONAL INDONESIA (SNI) TERHADAP INDUSTRI ELEKTRONIK RUMAH TANGGA DI SUMATERA UTARA (STUDI PADA PT. NEO NATIONAL MEDAN) - Roli Harni Yance S. Garingging; Runtung Runtung; Budiman Ginting; Mahmul Siregar (Universitas Sumatera Utara, 2014)
ABSTRACT Indonesian National Standard (SNI) was adopted by the International Standard Organization (ISO), the ISO adopted in particular fan of the International Electronic Commission (IEC). If businesses do not implement the SNI shall be sanctioned by Law No. 8 of 1999 on Consumer Protection. Problems arise when businesses are implementing SNI should produce in terms of trials to get SPPT-SNI. For example, be appointed PT. Neo National was to test the feasibility of the product quality brands such as Fan “SiJempol”. Products PT. Neo National was not obtained SNI, but TPPBJ Team (Team Supervisor Circulation of Goods and Services) found that the fan was in factory PT. Neo National has not been certified SNI. Therefore, PT. Neo National alleged to have committed violations of consumer protection in the field of producing goods that are not SNI. Provisions charged to PT. Neo National was Article 62 Paragraph (1) Jo. Article 8 Paragraph (1) Letter a and e. Law No. 8 of 1999 on Consumer Protection. In the meantime, to get SPPT-SNI, all businesses required to conduct due diligence on the quality Industrial Research Institute of Standardization. To test the feasibility of quality, these businesses also have to produce the goods samples for testing. This research was conducted to obtain legal certainty in the field of SNI for businesses who are implementing SNI. Barriers experienced by manufactures are SNI setting that overlap with consumer protection. Arrangements; Attitutde of PPNS-PK were unprofessional and proportionate; and Lact-disregard the Ministry of Industry in guiding businesses. Key Word : Indonesia National Standard; Consumer Protection; Implementation of SNI.